P-HPB-13: Spectrum of obscure common bile duct dilatation: Role of endoscopic ultrasonography - Dahale, Amol (Endosc Ultrasound, 2017)
BACKGROUND AND OBJECTIVES: Obscure dilated common bile duct (CBD) is not uncommon. Endoscopic ultrasound (EUS) has made diagnosis possible in most cases. Data on epidemiology on this entity are scarce. METHODS: This was a retrospective study conducted at GIPMER, New Delhi, between January 2014 and May 2015. Data of patients with obscure CBD dilatation were collected. Spectrum of diagnosis, baseline liver function tests (LFTs), radiological features (magnetic resonance cholangiopancreatography [MRCP]), and EUS findings were analyzed. RESULTS: Sixty patients (47 females) with mean age of 52 years (+/-14) were included. Thirty-one had abnormal LFT. Mean CBD diameter on MRCP was 9.8 mm. Pancreatic duct was dilated in five patients. EUS evaluation was helpful and made or predicted diagnosis in all patients. All diagnoses were confirmed on EUS-guided fine needle aspiration cytology (FNAC) or endoscopic retrograde cholangiopancreatography (ERCP) and follow-up EUS in few patients. Diagnosis was passed out CBD stone in 12 (20%), CBD stone in 9 (15%), periampullary diverticulum in 9 (15%), postcholecystectomy dilated CBD in 7 (11.7%), and malignancy in 8 (13.3%). The presence of intrahepatic biliary radicle dilatation (IHBRD) on radiological investigations was significant predictor (P = 0.04) for abnormal EUS findings. EUS saved ERCP and surgery in 25 patients. CONCLUSION: EUS is an excellent tool for obscure CBD dilatation. The presence of IHBRD predicts abnormal findings EUS.